Aging and Social Expenditure in the Major Industrial Countries, 1980-2025 - Ruggiero, Edgardo (Occasional Papers; Occasional Paper ;, 1986)
Most of the seven major industrial countries are now experiencing significant changes in their demographic structure. A persistent pattern of declining fertility and improving life expectancy has created major segments of the population that are already relatively aged or will become so in the near future. This paper examines the impact of prospective demographic trends on the level and structure of social expenditure by the governments of the seven major industrial countries (the Group of Seven) through the year 2025.